The cvn8 Conservon System Is a Global Regulator of Specialized Metabolism in Streptomyces coelicolor during Interspecies Interactions - Bailey Bonet (American Society for Microbiology, 2021)

(untitled)
Interactions between different species of actinomycete bacteria often trigger one of the strains to produce specialized metabolites, such as antibiotics. However, how this induction occurs at the genetic level is poorly understood.